The figure of the detective : a literary history and analysis - Brownson, Charles, 1945- (McFarland & Company, Inc., Publishers, 2014)
"This book begins with a history of the detective genre. The theory of the genre is laid out along with its central theme of the getting and deployment of knowledge. These changes explain the decay of the English Classic and its replacement by noir"--